Respuesta :
1st factor is 3x:
= 3x(x² - 8x + 15)
2nd & 3rd factors:
x² - 8x + 15 = 0
x² - 4x = - 15 + (- 4)²
x² - 4x = - 15 + 16
(x - 4)² = 1
x - 4 = 1
= x - 4 - 1, = x - 5
= x - 4 + 1, = x - 3
Answer: 3x(x - 5)(x - 3) are the factors.
Proof:
= 3x(x - 5)(x - 3)
= 3x(x² - 5x - 3x + 15)
= 3x(x² - 8x + 15)
= 3x³ - 24x² + 45x
= 3x(x² - 8x + 15)
2nd & 3rd factors:
x² - 8x + 15 = 0
x² - 4x = - 15 + (- 4)²
x² - 4x = - 15 + 16
(x - 4)² = 1
x - 4 = 1
= x - 4 - 1, = x - 5
= x - 4 + 1, = x - 3
Answer: 3x(x - 5)(x - 3) are the factors.
Proof:
= 3x(x - 5)(x - 3)
= 3x(x² - 5x - 3x + 15)
= 3x(x² - 8x + 15)
= 3x³ - 24x² + 45x
Answer: 3x(x-3)(x-5)
Step-by-step explanation:
The negative has to be consistance because of the earlier factoring